2019
DOI: 10.3390/su11236591
|View full text |Cite
|
Sign up to set email alerts
|

Indoor Environmental Quality Evaluation of Lecture Classrooms in an Institutional Building in a Cold Climate

Abstract: In this paper, ventilation, indoor air quality (IAQ), thermal and acoustic conditions, and lighting were studied to evaluate the indoor environmental quality (IEQ) in an institutional building at the University of Alberta in Edmonton, Canada. This study examined IEQ parameters, including pressure, illuminance, acoustics, carbon dioxide (CO2) concentration, temperature, and humidity, with appropriate monitors allocated during a lecture (duration 50 min or 80 min) in four lecture classrooms repeatedly (N = 99) f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 50 publications
(57 reference statements)
3
19
0
Order By: Relevance
“…Also, a positive correlation was found in T2 between students' academic development and contact with other students and teachers. Previous literature already pointed out the relationship between the variables studied and the academic development of students (Braat-Eggen et al, 2017;Hviid et al, 2020;Mcinnerney & Roberts, 2004;Piccoli et al, 2001;Sun et al, 2008;Zhong et al, 2019). In this line, our results confirm these relationships between the variables under the conditions of a pandemic and lockdown in engineering students.…”
Section: Effects Of the Prolonged Lockdown On Students' Learning Experiencesupporting
confidence: 90%
See 2 more Smart Citations
“…Also, a positive correlation was found in T2 between students' academic development and contact with other students and teachers. Previous literature already pointed out the relationship between the variables studied and the academic development of students (Braat-Eggen et al, 2017;Hviid et al, 2020;Mcinnerney & Roberts, 2004;Piccoli et al, 2001;Sun et al, 2008;Zhong et al, 2019). In this line, our results confirm these relationships between the variables under the conditions of a pandemic and lockdown in engineering students.…”
Section: Effects Of the Prolonged Lockdown On Students' Learning Experiencesupporting
confidence: 90%
“…Finally, although it had not received much attention in distance education literature before the pandemic, learning environment conditions, its ergonomics, and access to a quality internet connection are additional and indeed important variables to consider in distance learning. A workspace that does not offer the appropriate conditions represents a risk factor for comfort, well-being, and students' academic performance (Braat-Eggen et al, 2017;Hviid et al, 2020;Parvez et al, 2019;Zhong et al, 2019). The unexpected change to online education due to the COVID-19 pandemic has made researchers and academic staff wonder whether students were prepared to take classes from their home and whether they had an adequate workspace, equipment, and facilities for effective learning.…”
Section: Impact Of Covid-19 On Students' Learning Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Several studies about retrofitted school buildings with the implementation of measures in line with the Energy Performance of Buildings Directive have been conducted in Mediterranean countries, with the application of cost-optimal methods for designing strategies to achieve nearly zero-energy educational buildings [21]. Other authors focused on the link between energy retrofitting interventions and IAQ in school buildings [22,23]. Another study that was conducted on a school building [24] identified an IEQ index to be used as an indicator of comfort, health, and building management costs.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results show that the energy consumptions may be strongly reduced by decreasing the air flow rate by 50%, with slight variations in the IEQ. In a similar study, IEQ of lecture classrooms in an institutional building in a cold climate was evaluated by Zhong et al [6] through the artificial neural network method. They examined various parameters such as CO 2 concentration, acoustics, illuminance and humidity in four classrooms.…”
Section: Introductionmentioning
confidence: 99%